The Effect of an Educational Curriculum Using the Computer in Learning a Skill on the Parallel Device of the Artistic Gymnastics for Girls - Khamees Hameed, Sanaa (International Journal of Psychosocial Rehabilitation, 2020)
Given the characteristics of the computer that distinguish it from other educational means, the importance of the research emerges through the preparation of an educational curriculum that carries with it the possibility of learning your artistic gymnastics skills for girls through the use of computers in the learning process by presenting a correct model of the skills that will be learned. The research assumed there are statistically significant differences in the pre and posttests of the two groups (control and experimental) in learning some skills in the artistic sexuality of girls and in favor of the post tests. The researcher used the experimental method for its suitability to the nature of the problem. He concluded that the use of computers as an aid in the process of learning some skills in boxing achieved better results than the traditional method used in the faculties of physical education and sports sciences and is clearly evident in the rate of development obtained by them. He recommended the use of computers as an aid to learning some technical skills for girls.